2015
DOI: 10.17554/j.issn.2409-3548.2015.01.4
|View full text |Cite
|
Sign up to set email alerts
|

Venous and Arterial Thrombosis: Is there a Link?

Abstract: Following the demonstration that patients with deep venous thrombosis of the lower extremities have a significant higher prevalence of carotid plaques than matched control individuals, numerous studies have consistently shown that patients with venous thromboembolism -especially those with events of unknown origin -have a remarkably higher risk of developing subsequent arterial thrombotic events than control subjects. The two vascular disorders share several risk factors (including age, obesity, smoking habit,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 69 publications
1
4
0
Order By: Relevance
“…Our findings on proximal DVT are in line with previous case–control studies and a meta-analysis, 10 11 12 13 14 15 16 as well as a 2003 pilot study by Prandoni et al 1 It bears noting that an ABI £ 0.9 may also be an indicator of atherosclerosis at other vascular sites, and constitute a prognostic marker for cardiovascular events and functional impairment, even without any symptoms of peripheral arterial disease. 27 28 29 In fact, Libertiny and Hands reported that ABI is linked to an increased VTE diagnosis.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings on proximal DVT are in line with previous case–control studies and a meta-analysis, 10 11 12 13 14 15 16 as well as a 2003 pilot study by Prandoni et al 1 It bears noting that an ABI £ 0.9 may also be an indicator of atherosclerosis at other vascular sites, and constitute a prognostic marker for cardiovascular events and functional impairment, even without any symptoms of peripheral arterial disease. 27 28 29 In fact, Libertiny and Hands reported that ABI is linked to an increased VTE diagnosis.…”
Section: Resultssupporting
confidence: 91%
“…8 Milan et al conducted a case–control study on subjects older than 50 years to assess the prevalence of symptomatic or subclinical atherosclerosis in 100 unselected patients with unprovoked VTE, and compared it with that of 100 patients with provoked VTE and 100 matched controls free from VTE disorders 9 : the prevalence of atherosclerosis was higher in patients with VTE (especially with unprovoked episodes) than in controls. Several studies and a meta-analysis have indicated that subjects with VTE may be at increased risk for acute cardiovascular events, 10 11 12 13 14 15 16 which is consistent with VTE and arterial cardiovascular events sharing common risk factors (e.g., obesity, hypertension, smoking, and diabetes/hyperglycemia). 6 17 18 19…”
mentioning
confidence: 59%
“…Yet, several lines of evidence support an at least a partial overlap in the pathogenesis of VTE and CVD. From an epidemiological standpoint, this is well illustrated by a study that revealed that patients with unprovoked VTE present an estimated risk of atherosclerosis that is 5.1 and 14.5-fold higher than in patients with secondary VTE and healthy controls, respectively [7,57] and by the existence of conditions that increase the risk of both VTE and CVD such as APS [58] and SCD [9,59]. In addition, the cross-talk between the immune system, hemostasis and atherogenesis is being increasingly supported by experimental data [14,15,52,60].…”
Section: Plos Onementioning
confidence: 96%
“…Venous thromboembolism (VTE) encompasses deep vein thrombosis (DVT) and pulmonary embolism (PE), which together represent the third leading cause of vascular disease in the world [3]. Although it has been long recognized that the pathogenesis of these two conditions are based on distinct cellular and molecular pathways, the existence of common pathogenic pathways contributing to both CVD and VTE is suggested by (i) the sharing of risk factors such as obesity, smoking, hypertriglyceridemia [4]; (ii) the epidemiological association between CVD and VTE illustrated by the higher prevalence of CVD in patients with VTE even years after the venous event [5][6][7]; (iii) the fact that some inflammatory diseases such as sickle cell disease and antiphospholipid syndrome (APS) increase the risk of both conditions [8,9]; and, (iv) more recently, the demonstration that treatment strategies classically used for CVD can also benefit patients with VTE [10,11], and vice versa [12]. In this context, a lot remains to be learned about their shared and independent pathological mechanisms, whose identification could contribute to the identification of new therapeutic targets for both VTE and CVD [7,13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation